Lighting Optimization of Karawo Production House - Niniek Pratiwi; Abdi Gunawan Djafar (International Journal of Built Environment and Scientific Research, 2022)
Karawo embroidery processes are carried out without using machine technology. This research aims to optimize the lighting of the Gorontalo karawo fabric production house. The method used is by surveying, conducting direct measurements, and distributing questionnaires. A simulation is carried out using Dialux Evo 9.0 in existing conditions and after the addition of lights. Simulation measurement shows an average lighting value of 461.3 lux from 07.00 to 17.00. The result does not meet the SNI 16-7062-2004 for fine work, which is a minimum of 1000-2000 lux. Based on the measurements on the field, it was found that the lighting level only ranged from 22.19 lux to 30.78 lux. According to the karawo craftsmen, 33% had headaches and eye pain during the production process, and 33% had eye pain. Moreover, based on the simulation with the light on, the average intensity is 1107.4 lux and reached the specified standard.